18F-AmBF3-MJ9: A novel radiofluorinated bombesin derivative for prostate cancer imaging. Issue 7 (1st April 2015) - Pourghiasian, Maral; Liu, Zhibo; Pan, Jinhe; Zhang, Zhengxing; Colpo, Nadine; Lin, Kuo-Shyan; Perrin, David M.; Bénard, François
Graphical abstract: Abstract: A novel radiofluorinated derivative of bombesin, 18 F-AmBF3 -MJ9, was synthesized and evaluated for its potential to image prostate cancer by targeting the gastrin releasing peptide receptor (GRPR). AmBF3 -MJ9 was prepared from an ammoniomethyl-trifluoroborate (AmBF3 ) conjugated alkyne2 and azidoacetyl-MJ9 via a copper-catalyzed click reaction, and had good binding affinity for GRPR ( K i = 0.5 ± 0.1 nM). The 18 F-labeling was performed via a facile one-step 18 F– 19 F isotope exchange reaction, and 18 F-AmBF3 -MJ9 was obtained in 23 ± 5% ( n = 3) radiochemical yield in 25 min with >99% radiochemical purity and 100 ± 32 GBq/μmol specific activity. 18 F-AmBF3 -MJ9 was stable in mouse plasma, and was partially (22–30%) internalized after binding to GRPR. Positron emission tomography (PET) imaging and biodistribution studies in mice showed fast renal excretion and good uptake of 18 F-AmBF3 -MJ9 by GRPR-expressing pancreas and PC-3 prostate cancer xenografts. Tumor uptake was 1.37 ± 0.25%ID/g at 1 h, and 2.20 ± 0.13%ID/g at 2 h post-injection (p.i.) with low background uptake and excellent tumor visualization (tumor-to-muscle ratios of 75.4 ± 5.5). These data suggest that 18 F-AmBF3 -MJ9 is a promising PET tracer for imaging GRPR-expressing prostate cancers.